Pulsed characterisation of trapping dynamics in AlGaN/GaN HEMTs. Issue 22 (1st October 2013) - Nakkala, P.; Martin, A.; Campovecchio, M.; Laurent, S.; Bouysse, P.; Bergeault, E.; Quéré, R.; Jardel, O.; Piotrowicz, S.
Abstract : Time‐domain pulsed I – V measurements dedicated to characterising and modelling the time‐dependent trapping phenomena of wide band‐gap AlGaN/GaN high electron mobility transistors (HEMTs) are presented. The influence of temperature, electric field and their mutual interaction on trap activation and time constants are investigated and illustrated in the case of 2 × 75 × 0.15 µm 2 AlGaN/GaN HEMTs from the III–V Lab. These measurements show that the most influential parameter on trap activation is the electric field induced by the highest drain voltage V DS‐max reached during a pulse sequence, which leads to the drain current collapse. These characterisations are intended to develop and improve new nonlinear models of GaN HEMTs, taking into account the dynamics of traps for modulated signals.